Analisa Kinerja OFDM Menggunakan Teknik Pengkodean Hamming - Daud P Sianturi; Febrizal Febrizal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Orthogonal Frequency Division Multiplexing (OFDM) is a very efficient high speed data transmission technique in wireless communication technology. This paper discusses the performance of OFDM system using Hamming Code. OFDM system using BPSK modulation schemes, operating under various channel conditions. To imitate the practical applications in the real world Rayleigh channel, Rician channels are also considered in addition to the AWGN channel. The simulation is done to investigate the performance of the coded OFDM system over the uncoded OFDM system. It is seen that coding improves BER performance of OFDM system and hence in this work, Hamming Code is used as single error correction.Keywords : OFDM, BER, Hamming Code, AWGN, rayleigh and Rician channels.